The ANALYSIS OF FINANCIAL STATEMENTS OF THE REGIONAL GOVERNMENT OF DEMAK REGENCY FOR THE FISCAL YEAR 2016 - 2020 - Clara Yully Diana Ekaristi; Apip . (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
This study aims to determine the financial performance of the Demak district. The object of this research is the Demak Regency APBD Realization Report 2016-2020. The method used to collect secondary data is collected through the documentation stage. The data analyzed is in the form of the Demak Regency Government Budget Realization Report for the 2016-2020 fiscal year. The results showed that the financial statements of the Demak district government showed good performance but there were still some ratios that needed to be improved and improved, such as the independence ratio and the degree of fiscal decentralization.